The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1128/mbio.00207-16
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Component Regulatory System Impacts Extracellular Membrane-Derived Vesicle Production in Group A Streptococcus

Abstract: Export of macromolecules via extracellular membrane-derived vesicles (MVs) plays an important role in the biology of Gram-negative bacteria. Gram-positive bacteria have also recently been reported to produce MVs; however, the composition and mechanisms governing vesiculogenesis in Gram-positive bacteria remain undefined. Here, we describe MV production in the Gram-positive human pathogen group A streptococcus (GAS), the etiological agent of necrotizing fasciitis and streptococcal toxic shock syndrome. M1 serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
176
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(178 citation statements)
references
References 51 publications
2
176
0
Order By: Relevance
“…Thus, conserved Spo0A may be important for the regulation of vesiculogenesis in sporulating Gram-positive bacteria. Recently, it was reported that in the nonsporulating Gram-positive bacterium Streptococcus pyogenes, the two-component system CovRS downregulates MV formation (49). Given the results of our study, which indicates the phosphorylated/activated response regulator is required for MV production, signal transduction from sensor kinase to response regulator or two-component system could be a key regulatory system of vesiculogenesis in both sporulating and nonsporulating Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, conserved Spo0A may be important for the regulation of vesiculogenesis in sporulating Gram-positive bacteria. Recently, it was reported that in the nonsporulating Gram-positive bacterium Streptococcus pyogenes, the two-component system CovRS downregulates MV formation (49). Given the results of our study, which indicates the phosphorylated/activated response regulator is required for MV production, signal transduction from sensor kinase to response regulator or two-component system could be a key regulatory system of vesiculogenesis in both sporulating and nonsporulating Gram-positive bacteria.…”
Section: Discussionmentioning
confidence: 80%
“…EVs are enriched in sphingolipids ,phosphatidylethanolamine, with a higher component of unsaturated fatty acids. Remarkably their compositions were distinct from other bacterial EVs: EVs from Group A Streptococcus (42) displayed an enrichment in phosphatidylcholine and monoacylglycerol. Lipid composition of EVs may vary with the bacterial species and possibly is finely adapted for each environmental niche.…”
Section: Discussionmentioning
confidence: 91%
“…For Gram-positive bacteria these questions are further complicated by concerns as to how EV traverse the bacterial cell wall (23). Raising additional suspicion for their existence was the absence of EV-null mutants, although recent work have identified genes modulating EV synthesis in Gram-positive bacteria (42) and mycobacteria (43), and gene deletions that alter morphology of EVs (17). In this study we establish that EVs are associated with LLO via biochemical purification approaches, functional detection, immunoEM and fluorescence microscopy.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted in this study, the majority of EVs proteins were cytoplasmic in both G. adiacens and G. elegans proteomes (71% and 67% respectively). Cytoplasmic proteins located in other bacterial vesicles have been reported in several earlier studies [36, 38]. Existing evidence suggests that the enormous location of cytoplasmic proteins into vesicles is due to specific sorting mechanisms, and not due to lysis of dead cells [39].…”
Section: Resultsmentioning
confidence: 98%